2010
DOI: 10.1097/jto.0b013e3181f20ec4
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy for Thymic Neoplasms

Abstract: The role of radiotherapy (RT) in the treatment of thymoma and thymic carcinoma has been evaluated by many investigators over the past two decades. The low incidence of these neoplasms has limited most published studies to small series spanning long time intervals or extant population-based studies. The exact indications and protocols for the use of RT as a part of the multidisciplinary approach to thymoma and thymic carcinoma are still unclear. However, a review of recent literature shows potential benefits fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 61 publications
0
17
0
2
Order By: Relevance
“…Specifically, some advocate AT for all patients undergoing thymectomy, regardless of tumor features 23 or the data on completeness of resection or pathologic stage. 24 So far, prospective clinical trials on AT are limited, 25,26 and in some cases biased by including thymoma along with thymic carcinoma. 25 On the other hand, it is worthy of note that AT (mainly mediastinal radiotherapy) may be associated with adverse effects, including secondary malignancies, pulmonary fibrosis, coronary artery disease, cardiac valvular fibrosis, pericardial disease, and esophageal strictures.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, some advocate AT for all patients undergoing thymectomy, regardless of tumor features 23 or the data on completeness of resection or pathologic stage. 24 So far, prospective clinical trials on AT are limited, 25,26 and in some cases biased by including thymoma along with thymic carcinoma. 25 On the other hand, it is worthy of note that AT (mainly mediastinal radiotherapy) may be associated with adverse effects, including secondary malignancies, pulmonary fibrosis, coronary artery disease, cardiac valvular fibrosis, pericardial disease, and esophageal strictures.…”
Section: Discussionmentioning
confidence: 99%
“…6 Adjuvant radiation has been used in selected cases, although its role remains controversial. 7 In locally advanced and metastatic disease, a multimodality approach including chemotherapy, radiation therapy, and surgery has been used with some success, [8][9][10] although the optimal regimen and sequencing of treatments is based on expert opinion from phase II trials rather than randomized comparisons of therapeutic strategies.…”
mentioning
confidence: 99%
“…The expression of Kit was also used as a diagnostic tool of these tumors [39,93] [8,31,67]. Nine studies reported that the staging wasn't a relevant prognostic factor [6,9,19,20,30,46,57,71,74].…”
Section: Discussionmentioning
confidence: 99%